Journal of Human Services Abstracts. Volume 8, Number 4, October 1983 - Aspen Systems Corp., Rockville, MD.; Aspen Systems Corp., Rockville, MD. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
This journal provides abstracts of 150 documents included in the database of Project SHARE, a national clearinghouse for improving the management of human services. These documents are on subjects of concern, interest, and importance to those responsible for the planning, management, and delivery of human services. Topics include planning, health services, administration, counseling services, employment services, personnel management, vocational rehabilitation, services for the elderly and disabled, and day care. Abstracts are arranged in alphabetical order by title and include the following information: author, publication date, number of pages, order number, availability, and a summary of content. Other parts of the journal contain an alphabetical list of personal and corporate authors, an alphabetical list of document titles, and a subject index. The index is a guide to the abstracts by specific subject categories with cross-references from synonyms to preferred terms. (YLB)
Sponsoring Agency: Department of Health and Human Services, Rockville, MD. Project Share.
Contract Number: HHS-100-81-0052.
ERIC Note: For related documents, see ED 218 502, ED 221 673, ED 223 822, ED 231 977, and ED 236 378.
Journal of Human Services Abstracts, v8 n4 Oct 1983.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Abstracts; Administration; Annotated Bibliographies; Community Services; Counseling Services; Data Processing; Day Care; Delivery Systems; Disabilities; Employment Services; Health Services; Human Services; Information Sources; Mental Health Programs; Needs Assessment; Older Adults; Personnel Management; Planning; Program Descriptions; Program Development; Vocational Education; Vocational Rehabilitation; Volunteers; Project SHARE; Collected Works, Serials; Reference Materials, Bibliographies